Democratic Republic of the Congo : Request for a Three-Year Arrangement under the Poverty Reduction and Growth Facility and for the First Annual Program. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines the Democratic Republic of the Congo's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and for the First Annual Program. The authorities requested a three-year PRGF arrangement in support of their program covering April 1, 2002-July 31, 2005, in an amount equivalent to SDR 580 million. The authorities have also steadfastly implemented a Staff-Monitored Program covering June 2001-March 2002, aiming principally at stabilizing the economic situation, and laying the foundation for the restoration of growth and reconstruction.